Beyond Liberal Democracy: Diverse Educational Relations - Thayer-Bacon, Barbara J. (Paideusis, 2006)
This essay offers a critical analysis of Locke's and Rousseau's basic assumptions upon which classical liberalism is built: rationalism, universalism, and individualism. I then describe an alternative starting place for democracy with a transactional view of individuals-in-relation-to-others. I then offer specific educational examples to help me sketch two themes that illustrate problems with classical liberalism and how a transactional democracy-always-in-the-making can help to solve these problems.